3-phase dual-energy CT scan as a feasible salvage imaging modality for the identification of non-localizing parathyroid adenomas: a prospective study. Issue 1 (December 2015) - Roskies, Michael; Liu, Xiaoyang; Hier, Michael; Payne, Richard; Mlynarek, Alex; Forest, Veronique; Levental, Mark; Forghani, Reza
Abstract Objectives Accurate pre-operative imaging of parathyroid adenomas (PAs) is essential for successful minimally invasive surgery; however, rates of non-localizing PAs can be as high as 18 %. Multiphasic dual-energy CT (DECT) has the potential to increase accuracy of PA detection by enabling creation of paired material maps and spectral tissue characterization. This study prospectively evaluated the utility of 3-phase DECT for PA identification in patients with failed localizatio n via standard imaging. Methods Patients with primary hyperparathyroidism and non-localizing PAs underwent a 3 phase post-contrast DECT scan acquired at 25, 55, and 85 s. The scans were prospectively evaluated by two head and neck radiologists. Pre-operative localization was compared to intraoperative localization and final histopathology. A post-hoc DECT spectral density characterization was performed on pathologically-proven PAs. Results Out of 29 patients with primary hyperparathyroidism and non-localized PAs, DECT identified candidates in 26. Of the 23 patients who underwent parathyroidectomy, DECT provided precise anatomic localization in 20 patients (PPV = 87.0 %), one with multi-gland disease. The virtual unenhanced images were not found to be useful for diagnosis but successful diagnosis was made without an unenhanced phase regardless. Spectral analysis demonstrated a distinct spectral Hounsfield attenuation curve for PAs compared to lymph nodes on arterial phase images. Conclusion 3-phase DECT without an unenhanced phase is a feasible salvage imaging modality for previously non-localizing parathyroid adenomas. Optimal interpretation is achieved based on a combination of perfusion characteristics and other morphologic features. Advanced spectral DECT analysis has the potential for further increasing accuracy of PA identification in the future.